A promising tool for biomolecular nanotechnology – bionanoparticles. (1st January 2012) - Kumar, K. Pavan; Reddy, V. Chinnapa; Kumar, S. Vinod Hulle; Radhika, P.R.; Sivakumar, T.
Bionanoparticles are naturally produced entities that are of nanometre dimension. Viruses like cowpea mosaic virus (CPMV), cowpea chlorotic mottle virus (CCMV), turnip yellow mosaic virus (TYMV), tobacco mosaic virus (TMV), adenovirus, ferritin, and enzyme complexes exemplify these systems, with their precise arrangements of tens to hundreds of molecules into highly organised scaffolds for nucleic acid packaging, metal storage, catalysis or sequestering reactions at the nanometre scale. The purification method involves an efficient tangential flow filtration (TFF), diafiltration and various chromatographic techniques. The bionanoparticles are characterised by using the transmission electron microscopy, scanning electron microscopy and various spectrophotometric methods. One promising medical application of nanotechnology is the targeted delivery of pharmaceuticals to specific cells within an organism under minimisation of adverse effects for the remaining cells by nanoscale carriers. The branch of bionanotechnology in which naturally occurring nanoparticles are modified and manipulated for various applications is a rich and newly emerging field of research.